Pulses within pulses: Concentration‐discharge relationships across temporal scales in a snowmelt‐dominated Rocky Mountain catchment. Issue 9 (27th September 2022) - Hensley, Robert; Singley, Joel; Gooseff, Michael
Abstract: Concentration‐discharge (C‐Q) relationships can provide insight into how catchments store and transport solutes, but analysis is often limited to long‐term behaviour assessed from infrequent grab samples. Increasing availability of high‐frequency sensor data has shown that C‐Q relationships can vary substantially across temporal scales, and in response to different hydrologic drivers. Here, we present 4 years of dissolved organic carbon (DOC) and nitrate‐nitrogen (NO3 ‐N) sensor data from a snowmelt‐ dominated catchment in the Rocky Mountains of Colorado. We assessed both the direction (enrichment vs. dilution) and hysteresis in C‐Q relationships across a range of time scales, from interannual to sub‐daily. Both solutes exhibited a seasonal flushing response, with concentrations initially increasing as solute stores are mobilized by the melt pulse, but then declining as these stores are depleted. The high‐frequency data revealed that the seasonal melt pulse was composed of numerous individual daily melt pulses. The solute response to daily melt pulses was relatively chemostatic, suggesting mobilization and depletion to be progressive rather than episodic processes. In contrast, rainfall‐induced pulses produced short‐lived but substantial enrichment responses, suggesting they may activate alternative solute sources or transport pathways. Finally, we observed low‐level diel variation during summer baseflow following the melt pulse, likely driven by effects of daily evapotranspiration cycles. Additional contributions from in‐stream metabolic cycles, independent from but covarying with diel streamflow cycles, could not be ruled out. The results clearly demonstrate that solute responses to daily cycles and individual events may differ significantly from the longer‐term seasonal behaviour they combine to generate. Abstract : Utilizing high‐frequency sensor data, we examine concentration‐discharge relationships across temporal scales in a high‐elevation, snowmelt‐dominated catchment. We demonstrate how embedded within the larger seasonal snowmelt signal, are smaller individual pulses driven by daily melt cycles and rainfall, which have their own distinctly different enrichment or dilution responses and hysteresis patterns.